2008
DOI: 10.1111/j.1572-0241.2008.01956.x
|View full text |Cite
|
Sign up to set email alerts
|

T Cells in the Myenteric Plexus of Achalasia Patients Show a Skewed TCR Repertoire and React to HSV-1 Antigens

Abstract: These data suggest that the oligoclonal lymphocytic infiltrate within the LES of achalasia patients may represent the trace of an immune-inflammatory reaction triggered by HSV-1 antigens and that the Th1-type cytokines released by the activated lymphocytes may contribute to establish the neuronal damage accounting for the clinical features of idiopathic achalasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
109
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(123 citation statements)
references
References 56 publications
10
109
1
3
Order By: Relevance
“…The findings of the current study appear to differ from that conducted by Facco et al where they found no difference in the proliferation index of PBMCs of patients with primary achalasia compared to control subjects [7]. One possible explanation is that the control population in that study composed of heartbeating cadaveric organ donors who may have been given medications that have altered T-lymphocytic function.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The findings of the current study appear to differ from that conducted by Facco et al where they found no difference in the proliferation index of PBMCs of patients with primary achalasia compared to control subjects [7]. One possible explanation is that the control population in that study composed of heartbeating cadaveric organ donors who may have been given medications that have altered T-lymphocytic function.…”
Section: Discussioncontrasting
confidence: 99%
“…In primary achalasia, an inflammatory T-lymphocytic infiltrate reactive to HSV-1 antigens is present in the myenteric plexus [7]. By real-time PCR, we demonstrated the existence of a heightened systemic immune response to HSV-1 antigens in patients with the condition.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Other related symptoms are regurgitation and chest pain. Although the exact causes of achalasia are still not known [there are some suggestions to a possible autoimmune pathogenesis activated by herpes simplex viruses (1)], the medical community has long been aware of how to alleviate the related dysphagia even before fully understanding the pathophysiology of the disease.…”
mentioning
confidence: 99%